2020
DOI: 10.1021/acs.jchemed.0c00877
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Flocculation Capacities of Different Cations and Their Implications for Soil Structure and Sustainability

Abstract: A laboratory exercise was developed for the study of the effect of three cations (Al, Ca, and Na) on the flocculation and dispersion of soil particles. The exercise was designed for Soil Science undergraduate students in the second-course in the Agricultural Engineering and Environmental Sciences department at the University of Vigo. The students' exercise consisted of the addition of different concentrations of NaCl, CaCl 2 , or AlCl 3 to a kaolinite water suspension and to an agricultural soil water suspensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…Conde-Cid et al have developed a laboratory exercise that allows undergraduates in the major of Agricultural Engineering and Environmental Science to study the effect of different cations on the flocculation and dispersion of soil particles. 21 The experimental results collected by students were similar to those previously found by teachers, demonstrating the effectiveness of this approach. Similarly, Neel et al have demonstrated a mini wastewater purification plant including physical pretreatment steps followed by chemical treatment of mud using flocculation with FeCl 3 and a cationic polyelectrolyte.…”
Section: ■ Introductionsupporting
confidence: 76%
See 1 more Smart Citation
“…Conde-Cid et al have developed a laboratory exercise that allows undergraduates in the major of Agricultural Engineering and Environmental Science to study the effect of different cations on the flocculation and dispersion of soil particles. 21 The experimental results collected by students were similar to those previously found by teachers, demonstrating the effectiveness of this approach. Similarly, Neel et al have demonstrated a mini wastewater purification plant including physical pretreatment steps followed by chemical treatment of mud using flocculation with FeCl 3 and a cationic polyelectrolyte.…”
Section: ■ Introductionsupporting
confidence: 76%
“…From the perspective of undergraduate education, it is crucial to bridge the gap between theoretical knowledge and industrial application in chemistry, energy, and environmental fields. Conde-Cid et al have developed a laboratory exercise that allows undergraduates in the major of Agricultural Engineering and Environmental Science to study the effect of different cations on the flocculation and dispersion of soil particles . The experimental results collected by students were similar to those previously found by teachers, demonstrating the effectiveness of this approach.…”
Section: Introductionmentioning
confidence: 99%